Campus Carry Attitudes Revisited: Variations within the University Campus Community. (3rd July 2021) - Hassett, Matthew R.; Kim, Bitna
ABSTRACT: This study examined attitudes toward campus carry – a policy that would permit individuals to carry concealed firearms on a university's grounds if they possess a permit. Survey data were collected from a sample of 1, 380 members of a campus community – undergraduate students, graduate students, faculty, and staff – at a medium-sized public university in Pennsylvania whose legislation leaves the decision of campus carry up to the institutions. The majority of the sample reported non-supportive attitudes toward the implementation of campus carry. However, the degree of support and general attitudes toward the policy varied with undergraduate students having the most supportive attitudes of campus carry, followed by graduate students, staff, and then faculty. Certain demographic variables along with other campus-related variables, such as a fear of victimization, predicted campus carry attitudes. The research findings are discussed in terms of both research and policy implications.